All Days 2014
DOI: 10.2118/169727-ms
|View full text |Cite
|
Sign up to set email alerts
|

Snorre In-depth Water Diversion Using Sodium Silicate - Large Scale Interwell Field Pilot

Abstract: Here we report on in-depth water diversion using sodium silicate to increase oil recovery at the Snorre field, offshore Norway. A comprehensive qualification program revealed that the onset of gelation can be controlled; this was demonstrated in realistic core flood experiments as well as in a single well injection pilot. This paper highlights key design, response measurement plan and operational experiences from a large scale interwell field pilot of sodium silicate injection in a reservoir segment at the Sno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…An in-depth permeability restriction of approximately 40 m away from the wellbore and permeability reduction of more than 100 were achieved and confirmed by post-gelation fluid injectivity measurements and transient falloff tests (Skrettingland et al, 2012). An inter-well field pilot conducted in 2013 on the same field demonstrated operational success to perform large-scale sodium silicate gelant injection with no wellbore plugging, and confirmed the ability to control the gelation onset (Skrettingland et al, 2014).…”
Section: Water Shut-off Chemicalsmentioning
confidence: 79%
“…An in-depth permeability restriction of approximately 40 m away from the wellbore and permeability reduction of more than 100 were achieved and confirmed by post-gelation fluid injectivity measurements and transient falloff tests (Skrettingland et al, 2012). An inter-well field pilot conducted in 2013 on the same field demonstrated operational success to perform large-scale sodium silicate gelant injection with no wellbore plugging, and confirmed the ability to control the gelation onset (Skrettingland et al, 2014).…”
Section: Water Shut-off Chemicalsmentioning
confidence: 79%
“…A number of pilot studies in the North Sea have demonstrated in recent years that sodium silicate can be successfully employed to enhance recovery from producing fields (Skrettingland et al (2012(Skrettingland et al ( , 2014). Combined with these pilots, experimental laboratory work has given insight on activation conditions, core-scale behaviour, and chemistry of the poorly understood polymerization process (Icopini et al (2005); Stavland et al (2011)).…”
Section: Introductionmentioning
confidence: 99%
“…Combined with these pilots, experimental laboratory work has given insight on activation conditions, core-scale behaviour, and chemistry of the poorly understood polymerization process (Icopini et al (2005); Stavland et al (2011)). Several numerical simulation studies, based on a weak coupling of a reservoir flow modeling and a separate software module for chemical reactions, have been able to replicate the main characteristics of the observed behaviour (Hiorth et al (2016); Skrettingland et al (2014)). Since the development of silicate gels and the accompanying permeability reduction is essentially a coupled process, Trujillo et al (2018) recently proposed a fully implicit coupled chemical-compositionalflow implementation.…”
Section: Introductionmentioning
confidence: 99%
“…The combined use of silicate/polymer systems has been reported by Lakatos et al, (1999) for near wellbore matrix treatment but not for controlling water production in naturally fractured reservoirs. Stavland et al, (2011) conducted a laboratory evaluation of a silicate system for deep reservoir placement (Skrettingland et al, 2014(Skrettingland et al, , 2012; the laboratory results were modeled using a commercial simulator (Hatzignatiou et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…There are three field pilots on the NCS where sodium silicates have been used; one pilot on Gullfaks (Rolfsvåg et al, 1996), and two pilots on Snorre. The Snorre pilots include a one well (Skrettingland et al, 2012) and a two well pilots (Skrettingland et al, 2014). In these pilots, sodium silicate was placed in formation matrix, whereas our focus is on a high-conductivity fracture treatment (CNF reservoirs).…”
Section: Introductionmentioning
confidence: 99%